The Nature of Laminations in Cores from Kongressvatnet, Svalbard, Norway - Johnston, Emme (2009)
Emme studied a thin section of a core recovered from Lake Kongress in order to characterize the lamination stratigraphy. Her work suggests that the varves are chemical in nature.